Membuat Katalog Online sebagai Media Promosi Menggunakan Aplikasi AI Canva Pada Karang Taruna Rw.06 - Siti Nurdiani; Yamin Nuryamin; Muhammad Fahmi; Muhammad Rezki (Universitas Bina Sarana Informatika, 2024)
This community service aims to provide training to members of Karang Taruna in the skill of creating online catalogs using Canva as a promotional tool. Catalogs play a crucial role in promoting products sold by your business. However, in this internet era, catalogs should ideally be presented online to reach a wider audience. Hence, online catalogs (e-catalogues) can be a primary weapon to attract customers' interest in the items you sell. Karang Taruna is a youth organization actively involved in community development at the local level. Participants will be introduced to the use of Canva, including creating an account and selecting suitable templates for the purpose of creating online catalogs as a sales promotion medium. Various options of product catalog templates are available for use. Users can adjust paper size, change dimensions, and perform editing using various available features. Canva can be accessed via mobile applications or the website. Users can save design results in various file formats. Essentially, Canva can be used for free. However, users can also purchase premium features and gain unlimited access. They will be able to use these skills to promote Karang Taruna's activities and initiatives, as well as support sales efforts of products or services within their community. This training is expected to enhance Karang Taruna's competitiveness and positive impact in the local community.